2015
DOI: 10.1016/j.ufug.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Potential reduction in urban runoff by green spaces in Beijing: A scenario analysis

Abstract: a b s t r a c tUrban green space provides multiple ecological benefits, among which the reduction of rainfall runoff is important for sustainable urban development, particularly for cities experiencing severe flooding and water hazards. However, the effectiveness of urban green space in mitigating runoff has not been fully determined. We evaluated potential reductions in surface runoff associated with urban green space in central Beijing under a greening scenario using the Soil Conservation Service Curve Numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 38 publications
5
53
0
1
Order By: Relevance
“…Assessment methods of ecosystem services that only consider landscape quantity can increase the risk of overvaluing mitigation services. The Beijing municipality announced a goal of 55% total green coverage by 2020 (Yao et al, 2015). We suggest that urban greening should be implemented by increasing the quality of green areas as well as their quantity.…”
Section: Implications For Urban Landscape Designmentioning
confidence: 90%
See 1 more Smart Citation
“…Assessment methods of ecosystem services that only consider landscape quantity can increase the risk of overvaluing mitigation services. The Beijing municipality announced a goal of 55% total green coverage by 2020 (Yao et al, 2015). We suggest that urban greening should be implemented by increasing the quality of green areas as well as their quantity.…”
Section: Implications For Urban Landscape Designmentioning
confidence: 90%
“…The correctness of the IKONOS classification was 0.98, 1.00, 0.69, 0.82, and 0.35 for the impervious land, water, forest land, grass land, and bare land, respectively. The overall accuracy of the classification was 85.8%, and the kappa coefficient was 0.75 (Yao et al, 2015). We analyzed the result of landscape conversion from 2002 to 2012 and found that the mean area of landscape units was 1293 m 2 .…”
Section: Landscape Typesmentioning
confidence: 99%
“…The relevant equation is as follows: The flooding probability was distributed from a maximum value of 99.65% (where green space did not exist at all, the slope was minimum and maximum hourly precipitation was maximum) to a minimum value of 0% (Figure 4b). Flooding possibilities are minimized in the mountainous area with the steepest slopes according to the deduced function (2). The steepest areas in the Type 2 flooded area are not considered vulnerable to flooding, because those areas quickly withdraw the exceeded amount of rainfall to the neighboring gentle sloped areas.…”
Section: Characteristics Of Green Spacesmentioning
confidence: 99%
“…Increases in impervious surfaces are known to significantly influence the hydrological cycle [1]. Moreover, decreases of evapotranspiration and reduced rainwater infiltration can increase average runoff and peak runoff amounts [2][3][4]. Consequently, flooding in urbanized areas often results in huge losses of life and property.…”
Section: Introductionmentioning
confidence: 99%
“…It's worth noting that, most case studies are from practice of China, the number of papers is 66, accounting for 40.24%, far more than case studies from other background. For example, Sponge city practices in Beijing [59,60,61], Tianjin [62] etc. The type IV describes the development of new technologies, tools or approaches in this field, such as green roof [63,64], rain garden [65,66], urban hydrology [67], which includes 109 papers and represents 11.331%.…”
Section: Classification Of Research Typesmentioning
confidence: 99%